Knowledge of Oral Biopsy Procedure among Dental Interns at a Tertiary Hospital in Eastern Nepal - Keshwar, Shashi; Shrestha, Ashish; Sarraf, Deependra Prasad (Birat Journal of Health Sciences, 2023)
Introduction: Various diagnostic procedures are available to reach a diagnosis in case of oral lesions. Biopsy is one of the important tools for confirmatory diagnosis. It becomes imperative not only for dentists but future dentists to have adequate knowledge regarding oral biopsy procedures. Objective: To assess the knowledge of oral biopsy procedure among dental interns. Methodology: A web-based cross-sectional study was conducted among interns at College of Dental Surgery, B.P. Koirala Institute of Health Sciences. A questionnaire was prepared and Google Form link was shared with the signed-up participants via messaging apps; Viber and WhatsApp. The descriptive statistics were calculated using Microsoft Excel 2016. Results: Out of 54 participants, 53 (98.15%) and 50 (92.5%) of the interns knew about incisional and excisional biopsy respectively. Only 27 (50%) of them responded that every lesion should be sent for histopathological examination. Only 25 (46.3%) of the interns were aware that the removal of tissue by laser or electrosurgery can introduce artefacts or tissue distortion and 27 (50%) responded that punch biopsy generally produces few artefacts within the biopsied sample. Seventy seven percent of the interns responded that volume of the fixative should be two times the volume of the biopsy specimen, while 15 (27.78%) responded that normal saline could be used as a fixative. Conclusion: The present study revealed, dental interns had a good understanding regarding oral biopsy and also highlighted the need for further training and modifications in curriculum.